Africa in Soviet studies. Annual. [1968. Transl. from the Russ. by I. Gavrilov. Editor-in-chief: V.G. Solodovnikov] ("Nauka" etc., 1969)
With bibliogr. and tabs. Original title: Afrika v sovetskich issledovanijach. Ežegodnik. U.S.S.R. Academy of Sciences. Africa institute.